Gia ellada choris vaseis kai pyrinika (Mobilization for Peace and National Independence, 1986)
Colour photograph of two girls holding hands, smiling Anti-war and nuclear weapons campaign poster. Original title: Για ελλαδα χωρισ βασεισ και πυρηνικα PO-1472